COMMERCIAL DEVELOPMENTS OF TEXTILE SECTOR OF HARPUT REGION IN 19TH AND 20TH CENTURIES - Aksoy, Elif; Bulent, Esref (Anadolu Univ, 2019)
Located in a natural transition area, Harput has been an important cultural and trade destination with extensive transportation facilities throughout history. Harput city offered services to caravans for accommodation and trade activities because the city was located on important trade routes. The silkworm breeding fabric weaving, and workshop-type industrial activities were carried out in Harput in the 19th century and beyond. Weaving was the most important branch of industry of the region at that time. In the 19th century many non-Muslim merchants, such as the Fabrikatoryans, went abroad from Harput to see and develop new production techniques and methods in the weaving industry. Harput had become one of the most important centers by the late 19th and early 20th centuries in the silk and cotton textile fabrics called Caharkezi, Shib, Kutnu, Sevai, Muslin, Satin, Manusa, Bezayagi (Plain Weave) and Citari. The woven silk and cotton fabrics were sent to neighboring provinces and to Istanbul while they also met the needs of the people of the region. In this study, the commercial developments in the textile sector in Harput in the 19th and 20th centuries were mentioned and the production amount and transportation of various dresses produced in Harput region in that period were analyzed by years. For this reason, it was benefitted from various sources about the development of textiles in the Harput region, the shipment cost of the dresses in Harput city was calculated by years and the kurus money was divided by the number of pieces to obtain a unit price. In addition, the examples of silk fabrics woven in that period in Harput were presented and how advanced the fabric weaving was documented. Moreover, the amounts of weaving production and transportation of Harput region were compared with other regions that engaged in the weaving production and transportation in the Ottoman Empire in the 19th and 20th centuries and the informat ion obtained were presented in the relevant tables and graphics.
Keywords: Harput; Textile; Trade; Weaving; Dress